Ślady produkcyjne na cegłach profilowanych z placu Kolegiackiego w Poznaniu – próba rekonstrukcji dawnej wytwórczości strycharskiej - Antowska-Gorączniak, Olga; Lajsner, Włodzimierz (Folia Praehistorica Posnaniensia, 2021)
Medieval profiled bricks from the remains of the city parish church of St. Mary Magdalene in Poznań are a very important source of information about the brickmaking craftsmanship. The study attempts to identify production traces with specific stages of brick production (the process of forming and drying bricks), along with an attempt to reconstruct these operations that were used by the Poznań brickmakers. In addition to the analyzes related to the number of occurrences, the type of research material was defined, the criteria for isolating individual traces were described, the state of knowledge about brickmaking and analogies of fittings found in medieval buildings, mainly in the city of Poznań, were taken into account.